Influence of Hydrothermal Synthesis Condition on Structure and Microwave Properties of Srn+1TinO3n+1 Ceramics - Zhou, Huang; Wang, Jiangying; Liu, Jintao; Jin, Shengyong; Zhang, Jingji (Asian Journal of Chemistry, 2012)
Srn+1TinO3n+1 (n = 1, 2) ceramics were prepared by using hydrothermal synthesis derived powders and the influence of hydrothermal synthesis condition on microwave properties were investigated. The hydrothermally synthesized powders mainly form SrTiO3 and Sr(OH)2·mH2O. Grain size of the SrTiO3 decreases with increasing the concentration of KOH and reaction temperature, which lend itself to the formation of Srn+1TinO3n+1 during sintering. Srn+1TinO3n+1 ceramics prepared by using high concentration of KOH have lower permittivity and higher Q value, due to the formation of pure phase Srn+1TinO3n+1 and low porosity of ceramics.